Drug repositioning in thyroid cancer treatment: the intriguing case of anti-diabetic drugs - Greco, Alessia; Coperchini, Francesca; Croce, Laura; Magri, Flavia; Teliti, Marsida; Rotondi, Mario (Frontiers in Pharmacology, 2023)
Cancer represents the main cause of death worldwide. Thyroid cancer (TC) shows an overall good rate of survival, however there is a percentage of patients that do not respond or are refractory to common therapies. Thus new therapeutics strategies are required. In the past decade, drug repositioning become very important in the field of cancer therapy. This approach shows several advantages including the saving of: i) time, ii) costs, iii) de novo studies regarding the safety (just characterized) of a drug. Regarding TC, few studies considered the potential repositioning of drugs.On the other hand, certain anti-diabetic drugs, were the focus of interesting studies on TC therapy, in view of the fact that they exhibited potential anti-tumor effects. Among these anti-diabetic compounds, not all were judjed as appropriate for repositioning, in view of well documented side effects. However, just to give few examples biguanides, DPP-4-inhibitors and Thiazolidinediones were found to exert strong anti-cancer effects in TC. Indeed, their effects spaced from induction of citotoxicity and inhibition of metastatic spread, to induction of de-differentiation of TC cells and modulation of TC microenvironment. Thus, the multifacial anti-cancer effect of these compounds would make the basis also for combinatory strategies. The present review is aimed at discuss data from studies regardig the anti-cancer effects of several anti-diabetic drugs recently showed in TC in view of their potential repositioning. Specific examples of anti-diabetic repositionable drugs for TC treatment will also be provided.